Legal Protection for Mothers as Victims of Child-to-Parent Violence: A Study on Consumer Lifestyle as a Trigger - Anisah, Aura; Lewoleba, Kayus Kayowuan (Al-Risalah, 2026)
This study examines the causal factors of child-to-parent violence against mothers arising from consumerist lifestyles, as well as the effectiveness of criminal law protection for mother-victims in Indonesia. Employing a normative juridical approach, the analysis focuses on Law No. 23 of 2004 on the Elimination of Domestic Violence (PKDRT Law) and Law No. 11 of 2012 on the Juvenile Criminal Justice System (SPPA Law). The findings indicate that impulsive consumerism—driven by low financial literacy and social pressure—often escalates into frustration that manifests as physical and psychological violence against mothers. The PKDRT Law has yet to explicitly regulate active economic violence perpetrated by children, while the diversion mechanism under the SPPA Law creates a dilemma between safeguarding victims’ rights and rehabilitating juvenile offenders. Recommendations include revising Article 9 of the PKDRT Law, strengthening BAPAS social reports (Litmas) to incorporate financial literacy interventions, and implementing preventive programs through the Ministry of Women's Empowerment and Child Protection (KPPPA) in collaboration with the Financial Services Authority (OJK). This study contributes to filling the analytical gap on consumerism-driven child-to-parent violence (CPV) in Indonesia and enriches the discourse on restorative justice in Southeast Asia.